Development of right ventricular electromechanical dyssynchrony following surgical repair of tetralogy of Fallot in infants - McCrary, Andrew W.; Collins, Sydney D.; Spector, Zebulon Z.; Kropf, P. Andrea; Barker, Piers C. A.; Kisslo, Joseph; Forsha, Daniel E. (Frontiers in Pediatrics, 2025)
BackgroundIn adolescents and adults with tetralogy of Fallot (TOF), right ventricle (RV) electromechanical dyssynchrony (EMD) due to right bundle branch block (RBBB) is associated with reduced exercise capacity and RV dysfunction. While the development of RBBB following surgical repair of tetralogy of Fallot (rTOF) is a frequent sequela, it is not known whether EMD is present in every patient immediately following rTOF. The specific timing of the onset of RBBB following rTOF therefore provides an opportunity to assess whether acute RBBB is associated with the simultaneous acquisition of EMD.MethodsTransthoracic echocardiography with speckle tracking analysis for RV global longitudinal strain (GLS) and 12-lead ECG were performed prospectively on 20 infants following rTOF. Three apical RV views were obtained using analogous imaging planes to the standard LV views to provide a comprehensive evaluation. Regional RV GLS patterns were categorized as synchronous, EMD, or indeterminate. EMD was defined as an early-terminated septal contraction opposed by early stretch and post-systolic peak contraction in the activation delayed RV free wall. An indeterminate pattern was defined as a lack of fully synchronous contraction of all segments but not meeting criteria for EMD. Pre-rTOF echocardiograms and ECGs were analyzed to confirm the presence of synchronous contraction and a normal QRS pattern and duration prior to surgery.ResultsTwenty TOF infants (median age 87 days; 8 days from surgery to post-rTOF evaluation) demonstrated QRSd prolongation following rTOF (pre-rTOF 58 ± 9 ms; post-rTOF 97 ± 14 ms; p < 0.001) with new RBBB morphology in all but one patient. All pre-rTOF RV strain patterns were synchronous. Post-rTOF RV strain analysis showed EMD in 25% (5/20) and an indeterminate pattern in 40% (8/20) with the remaining 35% (7/20) maintaining a synchronous pattern, including the patient without RBBB. The EMD group had the lowest RV GLS following repair (p = 0.006).DiscussionAcquisition of acute QRS prolongation in a RBBB pattern is near-universal following rTOF but without matched or identical patterns of dyssynchrony, suggesting that variations in the time from electrical to electromechanical dyssynchrony potentially caused by differences in right bundle branch anatomy and injury may be relevant to electromechanical outcomes.